DEMANDS FOR WORKER'S RIGHTS: A TREATY LAW PERSPECTIVE - Ester Theresia Nauli Sibarani; Leonyd Augusta Pangkerego; Mikael Titirlolobi; Tri safitri; Winarny Tamarice Sirenden (Problematika Hukum, 2023)
Demands for workers' rights are an important issue in the world of work. A contract law perspective is one approach to considering employee rights claims. This research aims to analyze employee rights claims in terms of contract law. Collective agreements are the basis for regulating the relationship between workers and employers. Employee rights are regulated and protected by company agreements. Workers' rights demands cover various aspects, such as fulfilling salaries, benefits, reasonable working hours, safety and health guarantees, adequate leave, protection against discrimination, and guaranteed legal protection. From a contract law perspective, it is important to understand the elements contained in an employment contract, such as the principles of the contract, the conditions that must be fulfilled, as well as the rights and obligations of each party. In addition, applicable laws and regulations must also be considered when resolving disputes between workers and employers. This research method can be used in qualitative normative legal research with secondary data. The results of this research are expected to provide a better understanding of workers' rights and the legal protection available in employment contracts. In short, it emphasizes workers' rights in the world of work. This is an important matter and can be seen from the perspective of contract law. Employment contracts are an important means of protecting workers' rights. However, it is also important to continue to monitor legal developments and improveexisting regulations to better protect workers' rights.Keywords: Worker’s rights, contract law, employee rights, legal protection,